The strategy of choosing the location of the water in the conquests of the Messenger, may Allah bless him and grant him peace and its effect on bringing victory closer (Journal of Namibian Studies : History Politics Culture, 2023)
This study aims to explain the importance of the location of water in the conquests of the Prophet, may Allah’s prayers and peace be upon him, and its impact on making the event and bringing victory closer, by tracing those conquests historically and highlighting the location of the water in them, and its impact on the course of their events, starting with choosing a station for the soldiers to rest and equipping them with their needs of water, and passing through their review He promised them and counted them, ending with taking him as a camp to fight the enemy on the battlefield, and employing him in it by cutting off supplies from him, hastening his defeat, and bringing victory closer to the Muslims.